2016
DOI: 10.1242/jcs.186098
|View full text |Cite
|
Sign up to set email alerts
|

Cdk-dependent phosphorylation regulates TRF1 recruitment to PML bodies and promotes C-circle production in ALT cells

Abstract: TRF1, a duplex telomeric DNA binding protein, is implicated in homologous-recombination-based alternative lengthening of telomeres, known as ALT. However, how TRF1 promotes ALT activity has yet to be fully characterized. Here we report that Cdkdependent TRF1 phosphorylation on T371 acts as a switch to create a pool of TRF1, referred to as ( pT371)TRF1, which is recruited to ALT-associated PML bodies (APBs) in S and G2 phases independently of its binding to telomeric DNA. We find that phosphorylation of T371 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…Analysis of C-circle assays revealed that depletion of TRF1 resulted in a significant loss in the level of C-circles in GM847 cells (Fig. 4c,d), in agreement with previous finding14. Like Myc-tagged wild type TRF1, both Myc-tagged TRF1-T271A and Myc-tagged TRF1-T271D were able to rescue the level of C-circles in TRF1-depleted cells (Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Analysis of C-circle assays revealed that depletion of TRF1 resulted in a significant loss in the level of C-circles in GM847 cells (Fig. 4c,d), in agreement with previous finding14. Like Myc-tagged wild type TRF1, both Myc-tagged TRF1-T271A and Myc-tagged TRF1-T271D were able to rescue the level of C-circles in TRF1-depleted cells (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Analysis of indirect immunofluorescence revealed that depletion of TRF1 resulted in a significant reduction in the percentage of GM847 cells exhibiting colocalization of large PML bodies with TRF2 and hRap1 (Fig. 5a–d), in agreement with previous finding that TRF1 is required for the formation of APBs1314. We observed that among cells scored positive for APBs, the average number of APB foci per cell was about 1.5 (Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations